Jaringan Komunikasi dalam Event Branding ”Khayangan Festival” untuk Meningkatkan Citra Perusahaan Khayangan Residence - Eliza Kurnia D. W; Saidatul Fitriya; Yesi Maulidia; Rio Kurniawan (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the communication network structure in the Khayangan Festival using the Social Network Analysis (SNA) approach. The study used a quantitative method by utilizing data on communication relationships between involved actors, both internal and external to the festival organizer. Data were analyzed using UCINET and NetDraw software by measuring Degree Centrality, Betweenness Centrality, Closeness Centrality, Eigenvector Centrality, and network density. The results showed that the communication network formed had a centralized pattern, where communication and coordination flows were concentrated in several key actors. Mas Arslan emerged as the most central actor with the highest scores on all centrality indicators, indicating his role as a coordination center, information connector, and the most influential actor in the network. Density analysis showed a relatively dense network with high interaction intensity between stakeholders. In addition, the involvement of the community, sponsors, media partners, and local influencers acted as weak ties that expanded the reach of information and strengthened the event's branding. These findings indicate that the success of the Khayangan Festival was supported by an integrated communication network structure and effective management of information flows. This study provides practical implications for event management in designing network-based communication strategies to improve the effectiveness of event coordination and promotion.